The Impact of Social Media Marketing on Brand Equity: A Study of Fashion-Wear Retail in Sri Lanka - Jayasuriya, Nisha Anupama; Azam, S.M. Ferdous (International Review of Management and Marketing, 2018)
Appreciating the massive popularity of Facebook worldwide the purpose of this study was identifying the Facebook marketing activities that have impact on brand equity and studying the relative importance of each activity on brand equity creation. This paper reviews the literature on social media marketing, paying particular attention on Facebook marketing functions and its relationship with brand equity. Despite the popularity of social media, there are no adequate studies testing the relationship between social media marketing and brand equity until the last decade (Veloutsou,Cleopatra; Moutinho, 2009), still the dearth of empirical findings accelerates the scarcity of research in this area. In Asia Pacific region context, there is hardly any research on finding the relationship between FM and BE (Ahmed & Ibrahim, (2017), Ramsaran-Fowdar & Fowdar, (2013). This study brings together the brand management literature and the social media theory in a business context. In doing so, this study offer a new structured model based on theory that would enhance the knowledge on the relationship between Facebook marketing and brand equity. Considering the popularity of social media, this research will be limited for Facebook platform and future researcher can conduct the same research of all the leading social networking sites such as Linkedin, Instagram, Youtube and Twitter. Keywords: Social Media Marketing, Facebook Marketing, Brand Equity, Fashion-wear Industry JEL Classifications: M31, M37